(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the development of associative thinking in students through the use of innovative technologies. In today’s rapidly evolving digital era, the integration of modern technologies into the educational process plays a vital role in stimulating students’ thinking and fostering independent and creative approaches to learning. The article provides recommendations and practical approaches for enhancing associative thinking using interactive methods, digital applications, and multimedia tools.